Early Detection Health Education is Aware Of The Influence Of Attitudes In Preventing Breast Cancer In Grade VII Female Students - Kusyani, Asri; Vidhiastutik, Yusiana (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Breast cancer is one of the serious health problems worldwide, including in Indonesia. Breast health education plays an important role in increasing public awareness of the dangers of breast cancer, including in adolescents. The purpose of this study was to determine the effect of breast health education as an early detection system on attitudes about breast cancer prevention in grade VII students. This study design used a pre-experimental with a one group pre-test-post test design. The sample of this study was 51 students using a purposive sampling technique. Data were collected using an attitude questionnaire. Data analysis used the Wilcoxon Test with a significance level of 0.05. The results of the study showed that before being given education, 47 respondents (92%) had good attitudes, while a small portion of 4 respondents (8%) had bad attitudes. And after being given education, 42 (96%) respondents had good attitudes and a small portion (4%) 2 respondents had bad attitudes. The results of the data analysis p 0.000 0.05 then H1 is accepted, meaning that there is an effect of education on improving the attitudes of grade VII students. The results of the study showed that health education greatly influenced students' understanding and attitudes about breast cancer prevention by routinely performing BSE once a month after menstruation. In addition to health education, support from the surrounding environment starting from parents, health workers and peers also influenced understanding of attitudes about breast cancer prevention.